2007
DOI: 10.1111/j.1365-2044.2007.05025.x
|View full text |Cite
|
Sign up to set email alerts
|

Manual displacement of the uterus during Caesarean section

Abstract: SummaryNinety ASA 1 and 2 pregnant women with term singleton pregnancies and no maternal and fetal complications, scheduled for elective or emergency Caesarean section, were randomly allocated to group LT (15°left lateral table tilt, n = 45) and group MD (leftward manual displacement, n = 45). Subarachnoid block was established with a 25-gauge spinal needle at the L3-L4 interspace using 1.5 ml of 0.5% hyperbaric bupivacaine. A median sensory level of T6 was observed in both groups but the incidence of hypotens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(58 citation statements)
references
References 23 publications
2
50
0
4
Order By: Relevance
“…Two nonarrest studies found that manual left uterine displacement (which is done with the patient supine) was as good as, or better than, left lateral tilt in relieving aortocaval compression, as assessed by the incidence of hypotension and ephedrine use. 452,453 Respiratory Considerations. One study documented that the upper airways in the third trimester of pregnancy are smaller (supine mean difference 0.20; 95% confidence interval [CI] 0.06 to 0.35) compared with their postpartum state and to nonpregnant controls (LOE 5).…”
Section: Aortocaval Decompression To Improve Maternal Hemodynamics Anmentioning
confidence: 99%
“…Two nonarrest studies found that manual left uterine displacement (which is done with the patient supine) was as good as, or better than, left lateral tilt in relieving aortocaval compression, as assessed by the incidence of hypotension and ephedrine use. 452,453 Respiratory Considerations. One study documented that the upper airways in the third trimester of pregnancy are smaller (supine mean difference 0.20; 95% confidence interval [CI] 0.06 to 0.35) compared with their postpartum state and to nonpregnant controls (LOE 5).…”
Section: Aortocaval Decompression To Improve Maternal Hemodynamics Anmentioning
confidence: 99%
“…They also reported that the manikin tended to slide off the incline plane at angles above 30°. Several recent studies have indicated that manual left uterine displacement in the supine position is as effective as the left lateral tilt in relieving caval compression (14,15) . For these reasons, the present guidelines recommend performing manual left uterine displacement in the supine position before placing the patient in a left lateral tilt position (11) .…”
Section: Discussionmentioning
confidence: 99%
“…El yardımı ile uterus fundusu orta hattan yaklaşık 3,5 cm sola deviye edilebilir. Multiple travmalı hastada elle müdahelede sorun varsa, yattığı masa sola doğru eğilebilir veya hastanın sırtına yerleştirilen yastık veya yuvarlanmış bir battaniye de hastanın sola doğru yatmasını sağla-yacak ve böylece aortokaval kompresyon önlenerek, venöz dönüş minimal olarak etkilenecektir (23) .…”
Section: Uterusun Sola Itilmesiunclassified